Analisis Respon Hidrologi dan Kualitas Air DAS Cisangkuy: Hydrological Response and Water Quality Analysis of Cisangkuy Watershed - Mawar Kusumawardani; Yayat Hidayat; Kukuh Murtilaksono (Jurnal Ilmu Tanah dan Lingkungan, 2018)
Cisangkuy watershed has an important role as an environmental buffer and water supplier for Bandung city and Bandung district. Quantity and quality of river water need to be maintained in order to fulfill water needs. This study aimed to analyze the performance of SWAT model to predict hydrological response and water quality of Cisangkuy watershed and to analyze hydrological and water quality responses of land use management scenarios implied. The method used is modeling with SWAT hydrological model. The results showed that the model could be used to predict the hydrological response of Cisangkuy watershed with NSE calibration value of 0.38 (satisfactory) and NSE validation value of 0.43 (satisfactory). The establishment protected forest area, Technical Design of Land and Forest Rehabilitation (RTk-RHL) and coffee-based agroforestry scenarios showed a decrease of surface flow, rise in lateral flow and baseflow. Hydrological response of RTRW scenario indicated an increase in the surface flow and a decrease in lateral flow and baseflow. The highest decrease of N-organic, NO3, NH4, and NO2 content is showed by the implication of RTRW scenario.